A study of user information satisfaction on financial management information system - Hasri Mustafa @ Abdul Razak; Zulkarnain Muhamad Sori; Ayoib Che Ahmad; Norlida Mahussin (EuroJournals Publishing, Inc., 2024)
Information technology support service is likely to be a fundamental requirement for future organizations for their sustained existence. Many corporate organizations are now moving towards establishing IT department especially in the area of accounting information system. As a result, these organizations are in great needs for accurate information on the current system and end user’s need in order to be more effective and efficient in their operations. The present paper examines on the Sistem Maklumat Pengurusan Kewangan (SMPK) or Financial Management Information System in one of the oldest universities in Malaysia and tries to explain the User Information Satisfaction (UIS) in both system needs and system performance. While results on system needs-performance gap analysis highlighted the importance level of SMPK’s features on the side of end-users’ needs, Snake Diagram is used to visualize the ‘size’ of SMPK’s UIS. Results from factor analysis however, are used for further investigation in the regression analysis. The multivariate results showed that User-Self Confidence, System Output, User-Self Development, User-Support, System Operation, User-Self Reliance and Problem Response Time are significantly associated with UIS. Hence, any improvements of the SMPK’s features must be in line with these factors. This study is likely to benefit information technology division staffs in providing future reference for better SMPK ‘s internal control.